RNAi pathways in the recognition of foreign RNA: antiviral responses and host–parasite interactions in nematodes. (18th July 2013) - Sarkies, Peter; Miska, Eric A.
Abstract : The nematode Caenorhabditis elegans was the first animal for which RNAi (RNA interference) in response to exogenous triggers was shown experimentally and subsequently the molecular components of the RNAi pathway have been characterized in some detail. However, the function of RNAi in the life cycle of nematodes in the wild is still unclear. In the present article, we argue that RNAi could be used in nematodes as a mechanism to sense and respond to foreign RNA that the animal might be exposed to either through viral infection or through ingestion of food sources. This could be of potential importance to the life cycle of parasitic nematodes as they ingest RNA from different hosts at different points during their life cycle. We postulate that RNA ingested from the host could be used by the parasite to regulate its own genes, through the amplification mechanism intrinsic to the nematode RNAi pathway.